EGFR mutation-positive NSCLC: factors to consider when deciding first-line therapy. Issue 5 (3rd May 2020) - Hulo, Pauline; Coupez, Dahna; Denis, Marc G; Bennouna, Jaafar
ABSTRACT: Introduction : Advanced non-small-cell lung cancers with EGFR mutation belong to the models of solid tumors which revealed the concept of oncogene addiction. For that reason, first, second and third generation EGFR tyrosine kinase inhibitors (TKIs) are the major anti-cancer drugs used in this indication. Translational research is currently focused on induced mechanisms of resistance and aims to define the best first therapeutic option and the best multiline strategy. Areas covered : EGFR TKIs, alone or in combination, i.e. anti-angiogenic drugs or chemotherapy, have demonstrated their ability to improve median PFS and OS in large randomized phase 3 trials. All these combinations, now available in first-line for EGFR mutated advanced NSLC, need to integrate multiple factors like patients characteristics (age, co-morbidities, eligibility to platinum-based chemotherapy), presence of brain metastasis at diagnosis, and type of EGFR mutation. This review has 2 aims: (1) to discuss the current knowledge of therapies available in non pre-treated EGFR-mutated NSCLC; (2) to propose the best therapeutic option according to multiple parameters, either clinical or biological. Expert commentary : In 2020, we can affirm that osimertinib the first choice for patients with EGFR-mutated NSCLC. However, this has to be balanced with patient characteristics, type of EGFR mutation and new therapeutic options.